2004
DOI: 10.1007/s10009-002-0104-3
|View full text |Cite
|
Sign up to set email alerts
|

Directed explicit-state model checking in the validation of communication protocols

Abstract: The success of model checking is largely based on its ability to efficiently locate errors in software designs. If an error is found, a model checker produces a trail that shows how the error state can be reached, which greatly facilitates debugging. However, while current model checkers find error states efficiently, the counterexamples are often unnecessarily lengthy, which hampers error explanation. This is due to the use of "naive" search algorithms in the state space exploration. In this paper we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
158
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(159 citation statements)
references
References 35 publications
1
158
0
Order By: Relevance
“…This is done using fixed points on symbolic set of states, and amounts to performing a BFS-based emptiness check. Whether based on nested DFS or SCC, explicit or symbolic, these emptinesscheck procedures can be simplified according to the strength of the automaton representing the property to check [2,13,6,23,1].…”
Section: Büchi Automata and Their Strengthsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is done using fixed points on symbolic set of states, and amounts to performing a BFS-based emptiness check. Whether based on nested DFS or SCC, explicit or symbolic, these emptinesscheck procedures can be simplified according to the strength of the automaton representing the property to check [2,13,6,23,1].…”
Section: Büchi Automata and Their Strengthsmentioning
confidence: 99%
“…In most of the approaches suggested so far the improvements have only concerned (inherently) weak or terminal automata: if an automaton contains at least one strong SCC, a general emptiness check is required, even if it also contains SCCs of inferior strengths. However Edelkamp et al [13] have suggested to consider the strengths of the SCCs to limit the scope of the nested DFS to the strong SCCs.…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Directed model checking techniques [10,11] try to direct the state space search to avoid the potential blowup faced by uninformed model checking techniques. Various heuristic strategies [9,13,15] have been proposed for searching the state space efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Directed explicit-state model checking [13] enhances the error-reporting capabilities of model checkers. The application of guided search for checking liveness properties is restricted to the reduction of trails [14].…”
Section: Introductionmentioning
confidence: 99%